Functional magnetic resonance imaging study of working memory several years after pediatric concussion. (6th June 2020) - Brooks, Brian L.; Virani, Shane; Khetani, Aneesh; Carlson, Helen; Jadavji, Zeanna; Mauthner, Micaela; Low, Trevor A.; Plourde, Vickie; MacMaster, Frank P.; Bray, Signe; Harris, Ashley D.; Lebel, Catherine; et al.
ABSTRACT: Primary objective: The neurophysiological effects of pediatric concussion several years after injury remain inadequately characterized. The objective of this study was to determine if a history of concussion was associated with BOLD response differences during an n-back working memory task in youth. Research Design: Observational, cross-sectional. Methods and Procedures: Participants include 52 children and adolescents (M = 15.1 years, 95%CI = 14.4–15.8, range = 9–19) with past concussion (n = 33) or orthopedic injury (OI; n = 19). Mean time since injury was 2.5 years (95%CI = 2.0–3.0). Measures included postconcussion symptom ratings, neuropsychological testing, and blood-oxygen-dependent-level (BOLD) functional magnetic resonance imaging (fMRI) during an n-back working memory task. Main Outcomes and Results: Groups did not differ on accuracy or speed during the three n-back conditions. They also did not differ in BOLD signal change for the 1- vs. 0-back or 2- vs. 0-back contrasts (controlling for task performance). Conclusions: This study does not support group differences in BOLD response during an n-back working memory task in youth who are on average 2.5 years post-concussion. The findings are encouraging from the perspective of understanding recovery after pediatric concussion.